Épocas de aplicação de indutores de resistência no controle de Meloidogyne javanica na cultura da soja - Puerari, Heriksen Higashi (2012)
Plants exhibit several forms of endogenous protection about different pathogen types, this protection forms sometimes are inactive, requiring the use of inducing molecules to its activation. For this reason, the use of resistance inducers may be a complementary method of disease control, among them, those related to the nematode presence. Therefore, this study aimed to evaluate different application periods of resistance inducers in soybean crop to Meloidogyne javanica control. For this purpose, plantlets of soybean susceptible cultivar BRSMT-Pintado and resistant cultivar MG/BR 46 Conquista were sprayed with acibenzolar-S-methyl/ASM (Bion 500®, Syngenta), citric biomass (Ecolife®, Quinabra) or manganese phosphite at three different times: seven days before, one day before or seven days after inoculation with 2000 eggs per plant. Untreated inoculated plants and untreated non-inoculated plants were used as controls. The experiments were conducted in two different periods: 10/23/2011 to 01/23/2012 and 12/05/2011 to 03/05/2012, named Experiments 1 and 2, respectively and carried out in greenhouse. Sixty days after, were analyzed nematological parameters, such as number of galls and eggs per gram of roots even as vegetative parameters in each treatment. The experiments were conducted in completely randomized design with 11 treatments and six replicates. The data obtained for each cultivar were subjected to variance analysis and the averages were compared by the Tukey test at 5% probability. The study demonstrated that in Experiment 2 which was applied ASM with seven days before inoculation was efficient to reduced M. javanica reproduction in soybean plant, independent of the cultivar susceptibility. However, the greatest plant development was only seen to susceptible soybean cultivar in Experiment 2. The commercial product Ecolife® decreased eggs number per gram of roots to M. javanica notably, when it was applied one or seven days before inoculation in susceptible soybean. The manganese phosphate was efficient to reduce the eggs number of pathogen in Experiment 1 to resistant soybean when it was applied seven days before the inoculation. None of this products presented considerable improvement in vegetal development.